The image of Algerian women during the popular movement A semiological analysis of photos on Face book - BENMABROUK, Fayçal; BOUGUERRA , Radouane (Journal of Social Sciences and Humanities, 2021)
Our study focuses on the semiological analysis of the image of Algerian women through several pictures published on the social networking site (Face book) in which Algerian women appear during the rallies of the popular movement that started three weeks ago. March 8, 2019 in Algeria .As for the selection of pictures, we have relied in this on the most important moments and shots in which this Algerian woman has appeared in a large way, as an expression and a more representative of the various sects of women in society. We focused on two pictures on a model of elderly women who represents the struggling woman, similar to the icon of the liberation revolution, Jamila BOUHAIRED, as well as the old woman who carries a national flag dating back to the date of the November Revolution with the blood of the martyrs on it, and the other two images represent the first forty years wearing a traditional haircut and the second representing an expressive image on solidarity between women demonstrators and men maintaining order. It should be noted that we have adopted Roland BARTHES and Martine JOLY approach to the semiological analysis of the digital image. Finally, we reached a set of important conclusions